Apendicitis aguda en niños: índice neutrófilo/linfocito como ayuda en el diagnóstico de peritonitis: revisión sistemática - Maldonado Morales, Heidy Mayely (2024)
Acute appendicitis, which is the main reason for urgent surgical interventions in young people, requires early diagnosis to prevent serious complications, such as peritonitis. In Ecuador, between 2012 and 2017, 38,533 cases were registered, having great impact in morbidity rates. This paper focuses on the neutrophil-lymphocyte index (INL) as a non-invasive predictor to help identify the risk of peritonitis in children with suspected acute appendicitis. In the methodology, adopting a systematic review design, it was stablished eligibility criteria for the bibliographic search from 2015 to 2023, prioritizing studies in Spanish and English and children aged 0 to 18 years, also using MESH terms and Boolean operators (And) in sources such as Lilacs, Scielo and Pubmed to ensure completeness and accuracy. Data collection and extraction guided by search tools such as Covidence and Rayyan in addition to the PRISMA diagram, provided us with 15 articles that were subsequently evaluated for quality using the JBI tool. The results revealed its high sensitivity and specificity, being specific compared to other markers and clinical tests in the differentiation of complicated vs uncomplicated cases. The visual presentation is summarized in an appealing poster that highlights its relevance in clinical decision-making, especially in the early detection of peritonitis in children suffering this pathology. In conclusion, INL contributes to the diagnosis of acute appendicitis accurately compared to other inflammatory markers. Its easy availability, low cost and high sensitivity position it as a valuable tool in the paediatric clinical setting. And, despite being favourable as it is a non-invasive clinical examination, it is emphasized to integrate the interpretation of the INL in the complete clinical evaluation